Dual drug delivery and sequential release by amphiphilic Janus nanoparticles for liver cancer theranostics. (October 2018) - Zhang, Lingyu; Zhang, Manjie; Zhou, Li; Han, Qinghe; Chen, Xiangjun; Li, Shengnan; Li, Lu; Su, Zhongmin; Wang, Chungang
Abstract: Co-delivery of two drugs with diverse physicochemical properties and specific administration order for cancer theranostics are vitally important for drug resistance conquering and side effects reducing. Consequently, we explored a unique amphiphilic PCL-AuNC/Fe(OH)3 -PAA Janus nanoparticle (JNP) to simultaneously preserve the hydrophilic drug (doxorubicin) and hydrophobic drug (docetaxel) in their distinct domains. Owing to their extraordinary heterostructure and independent pH and NIR sensitive properties, the optional sequential drug release by a single inorganic JNP was realized for the first time, and the results presented the synchronous release of two drugs had 5% better therapeutic effect. In addition, the excellent computed X-ray tomography/magnetic resonance (CT/MR) imaging capabilities from AuNC and Fe(OH)3 suggested our JNPs could effectively guide the cancer therapy. Furthermore, the mice treated with dual drug loaded PCL-AuNC/Fe(OH)3 -PAA JNPs under near infrared (NIR) laser irradiation showed better tumor inhibition than solo drug, cocktail and dual drug treated groups, indicating the effectivity and significance of combined cancer therapy. Graphical abstract: A unique cage-sphere like amphiphilic PCL-AuNC/Fe(OH)3 -PAA Janus nanoparticle is synthesized by a facile method, and it is designed to load hydrophobic and hydrophilic drugs in its two independent PCL-AuNC and Fe(OH)3 -PAA domains, respectively, to realize the control of release order by pH and NIR stimuli, CT and MR imaging and chemo-photothermal combined cancer therapy. Image 1